Retaining public enterprise status through own shares - Kocbek, Marijan (Lex localis, 2011)
The paper deals with the transitory provision of the public-private partnership act that strongly interferes with the legal status of the public enterprises in Slovenia. According to this Act, there are merely two options for public enterprises in which there are private equity stakes. A public enterprise can be transformed into a company in accordance with the Companies Act, or the public enterprise status can be retained, provided that the private equity stakes are in a way nullified in the public enterprise, and that only the equity stakes owned by the Republic of Slovenia or local communities remain. The Act expressly refers to an option of terminating the private equity stakes through an own shares fund. By analysing the Companies Act, the author states that in practice, the procedure for acquiring own shares is most relevant due to their withdrawal.
Keywords: delnice; javna podjetja; javno-zasebno partnerstvo; own shares; public enterprise; public-private partnership; Slovenia; Slovenija